Use of landscape ecological analysis to determine ecotone locations: an evaluation based on field data - Devi N. Choesin (Jurnal Matematika & Sains, 2001)
The moving split-window (MSW) technique, a landscape ecological method to detect ecotone or landscape boundary location, is described as an alternative to the use of conventional vegetation analysis. The effectiveness of MSW was tested by applying it to vegetation transect data collected from the field. While MSW analysis is practical and easily interpretable, results indicate that this method tended to overestimate minor shifts in species composition at the community level. For more accurate results, MSW must still be supported by information at the community level (e.g., by ordination), and an alternative method must be developed which makes use of the strengths of available methods.